ZONEAMENTO AGROECOLÓCO DO MUNICÍPIO DE SOUSA-PB - Almeida, Juciê de Sousa; Nascimento, Karoline Nóbrega Fabião do; Pereira, Rafaela Alves; Melo, Wellington Ferreira de (Caderno Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
_